2020
DOI: 10.1016/j.econmod.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Do policy burdens induce excessive managerial perks? Evidence from China’s stated-owned enterprises

Abstract: This paper explores the effect of policy burdens of China's state-owned enterprises (SOEs) on senior executives' excessive perks. The empirical analysis demonstrates that SOE policy burdens are significantly and positively correlated with senior executives' excessive perks, indicating that SOE policy burdens increase agency cost. The results hold after controlling for potential endogeneity. Moreover, we find the following evidences. Strategic policy burdens of SOEs have a significantly greater impact on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…To explore the impact of returnee executives on excess perquisite consumption , referring to prior research (Jian et al, 2020; Li, Yao, et al, 2020; Zhang et al, 2015), we first controlled for multiple variables at the firm level. We controlled for firm size , measured as the natural logarithm of total assets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the impact of returnee executives on excess perquisite consumption , referring to prior research (Jian et al, 2020; Li, Yao, et al, 2020; Zhang et al, 2015), we first controlled for multiple variables at the firm level. We controlled for firm size , measured as the natural logarithm of total assets.…”
Section: Methodsmentioning
confidence: 99%
“…Scholars have mainly explored the antecedents of excess perquisite consumption from the perspective of corporate governance characteristics. These studies found that internal corporate governance mechanisms (e.g., large shareholders and the board of directors) (Chen et al, 2019; Hermalin, 2005; Jian et al, 2020; Li, Yao, et al, 2020; Zhang et al, 2015) as well as external governance mechanisms (e.g., analyst coverage and labor unions) significantly influence TMTs' excess perquisite consumption (Chen et al, 2022; Cho et al, 2012). Numerous studies have shown that TMTs have an intrinsic motivation to pursue their own interests in contemporary firms in which ownership and control are categorized (Boubaker et al, 2017; Boubaker & Sami, 2011; Zhong, Ren, & Song, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Explained variable: Managerial perks is measured in logarithms (LNMP). This paper collects the detailed items of "Other Cash Paid Related To Business Activities" in the notes of the company's annual statements (Jianhui, Li, Meng, & Zhao, 2020;Liu, Wang, Zhang, & Zhang, 2012). Within these items, eight types of expenses that may be closely related to managerial perks are extracted: office expenses, travel expenses, business invitation expenses, communication expenses, overseas training expenses, board of directors' fees, car expenses and conference expenses.…”
Section: Methodsmentioning
confidence: 99%
“…The pay level of employees in SOEs in China is too high compared to private enterprises, the mobility of employees in stateowned enterprises is poor, and the degree of labor market constraints is low. Previous studies have shown that high wages are due to the excessive welfare of employees in SOEs (Bai et al, 2019;Jian et al, 2020;Kong et al, 2020), an important factor in aggravating the low efficiency of SOEs and is inconsistent with the basic assumptions of the efficiencywage theory. H1: Employee compensation restriction increases labor productivity in state-owned enterprises.…”
Section: Hypothesis Developmentmentioning
confidence: 99%